(untitled) (Philosophy and Progress, 2019)
Very few studies are available to understand the philosophical views of Rabindranath Tagore in the light of his attitude and realization of Islam vis-à-vis idea of universalism. Fact remains that the Islamic civilization has thoroughly been recognized in the academic circles but its depth and learning have not been studied up to expectation. European historians and philosophers seem to be hesitant to acknowledge the contribution of Islamic civilization over the centuries. Even a majority of Eastern scholars are critical about welcoming the actual merit of Islam. Rabindranath Tagore being one of the brightest stars in the galaxy of poets and writers made a serious study on the philosophy and writings of many Muslim thinkers and ultimately brought to our notice an extraordinary feeling about Islamic ideas and philosophy. Rabindranth Tagore seems to have sought the inner meaning of Islam and developed a kind of value- based attitude towards human life and the universe. It is likely that through his Gitanjali and Religion of Man (Manusher Dharma) in particular were presented with an objective to stimulate and guide men in search of Ultimate Truth and Oneness of God. It is said that Rabindranth Tagore was acquainted with the verses of the Qur‟an in his childhood and in this respect his father Maharishi Devendranath Tagore imbibed in him many theological aspects of Islam as a religion. The paper intends to explore how Tagore was influenced by Islam and as a poet-thinker he nurtured the idea of eternal truth from the Upanishads, the Tripitakas as well as the Bible and through a particular discipline and inner uplift he came to the conclusion that aggregate of essentials of diversity cannot be judged in the light of mere logic and arguments. This feeling seems to have prompted Tagore to find out the inner truth of the universe and side by side to propagate the idea of universal humanism throughout the world. Philosophy and Progress, Vol#61-62; No#1-2; Jan-Dec 2017 P 53-66